Liquidity and Stock Returns: Evidence from the UK Market - HUANG, SHAOHUA (2015)
The existence of liquidity premium has been supported by much evidence from various empirical studies which use different liquidity measures, especially on the US stock market. However, few empirical studies focus on UK stock market. Therefore, the liquidity effect on UK stock returns needs more evidence to support. In this study, two common liquidity measures are used. One is turnover rate,capturing the trading quantity dimension. Another one used in robustness test is the bid-ask spread, which captures the transaction cost dimension. By employing these two liquidity proxies, the purpose of this study is to test whether the UK stock market shows a liquidity premium over the 10 years period from July 2002 to June 2012. In the time-series portfolio analysis, not only CAPM model but also the Fama-French three-factor model is used to control the size and book-to-market effects. Results from the time-series portfolio analysis show that although there are other factors would affect stock returns in the UK stock market, the liquidity factor still explain some time series variations in stock returns.